2014
DOI: 10.1590/s1516-8913201401485
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the production of extracellular α-amylase by Kluyveromyces marxianus IF0 0288 by response surface methodology

Abstract: (up to 13-fold) in the production of extracellular α-amylase. These results constituted first evidence that K. marxianus could be potentially used as an effective source of extracellular α-amylase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…In previous studies, other researchers have tried amylase optimization using the RSM method. Roy and Mukherjee, 37 Keharom et al 38 and Stergiou et al 39 found positive effects of starch, Zambare 40 and Mustafa et al 41 found positive effects of temperature, and Gangadharan et al 42 found positive effects of CaCl 2 on amylase production using RSM method. The variables of probability p-value <0.05 were considered significant, and p-value higher than 0.05 were not considered significant.…”
Section: One Variable At a Time Approach And Plackett-burman Designmentioning
confidence: 99%
“…In previous studies, other researchers have tried amylase optimization using the RSM method. Roy and Mukherjee, 37 Keharom et al 38 and Stergiou et al 39 found positive effects of starch, Zambare 40 and Mustafa et al 41 found positive effects of temperature, and Gangadharan et al 42 found positive effects of CaCl 2 on amylase production using RSM method. The variables of probability p-value <0.05 were considered significant, and p-value higher than 0.05 were not considered significant.…”
Section: One Variable At a Time Approach And Plackett-burman Designmentioning
confidence: 99%
“…Kluyveromyces marxianus IF0 0288 at pH 6.13 produces the highest quantity of alpha-amylase. 49 The optimized pH for the production of alpha-amylase by Penicillium notatum IBGE 03 has been reported to be 5.5. 42 Also, Bacillus sp.…”
Section: Alpha-amylase Productionmentioning
confidence: 99%
“…Several reports exist of successful RSM application, with methodologies like the Box-Behnken design, Plackett-Burhman factorial design, and central composite design (CCD), for process parameter optimization and attainment of enhanced enzyme production ([ [34] , [39] , [40] , [41] ]; Paul et al., 2021). RSM has been applied successfully for enhanced alpha-amylase production [ [4] , [42] , [43] , [44] , [45] , [46] ].…”
Section: Introductionmentioning
confidence: 99%